Chronic gastritis: from histological protocol to substantiation of etiopathogenetic therapy - I. V. Dolgalev; E. N. Kareva; E. A. Lyalyukova; N. V. Pavlova (Лечащий Врач)
Gastritis is a reaction of the mucous membrane (MM) of the stomach to damage and is characterized by the formation of inflammatory, dystrophic and dysregenerative changes in the MM of the stomach, as well as atrophy of epithelial cells with replacement of normal glands with fibrous tissue. The progression of chronic gastritis (CG) is accompanied by the development of MM atrophy, dysplasia and becomes a significant factor in the formation of gastric malignant neoplasms. The article presents the modern etiological classification of CG, approaches to the diagnosis of CG, assessing the stage of gastritis on a scale of progressive increase in the likelihood of developing stomach cancer, presents the histological characteristics, and also substantiates etiopathogenetic approaches to the treatment of various forms of CG, including methods for optimizing the eradication therapy of H. pylori infection. which can be used to increase the effectiveness of not only standard triple therapy, but also other anti-Helicobacter treatment regimens. The use of proton pump inhibitors in the treatment of gastritis is considered.